(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
The metaphor of a marching platoon is presented by Pisani in Geolinguistica e indeuropeo to describe how a language works and changes. This is an original and relevant contribution of his own. The image bestowes plastic vividness to a central core of Pisani’s thinking: within the polarity between the individual and social aspect there lie the everchangeable and dynamic balance of a language and the principle itself of its changeability. The image outstands for its effectiveness and exhaustivity, as well as for the theoric supplementary contribution it offers to the description of a language. KEYWORDS: Pisani, history of linguistics, metalanguage, language change, metaphor